2018
DOI: 10.1186/s12920-018-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of in silico prediction tools for the classification of rare BRCA1/2 missense variants in clinical diagnostics

Abstract: BackgroundThe use of next-generation sequencing approaches in clinical diagnostics has led to a tremendous increase in data and a vast number of variants of uncertain significance that require interpretation. Therefore, prediction of the effects of missense mutations using in silico tools has become a frequently used approach. Aim of this study was to assess the reliability of in silico prediction as a basis for clinical decision making in the context of hereditary breast and/or ovarian cancer.MethodsWe tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 37 publications
12
73
1
Order By: Relevance
“…In a previous study, using a small dataset of BRCA2 variants, Karchin, Agarwal, Sali, Couch, and Beattie () find that general tools display good sensitivities but low specificities. A similar trend has been recently reported by Ernst et al (), after testing PolyPhen‐2, SIFT, Align‐GVGD, and MutationTaster2 in a set of 236 BRCA1/2 variants. These authors express concern about the moderate performance observed, particularly about the low specificities observed relative to HBOC diagnosis requirements (e.g., PolyPhen‐2: 0.67 and 0.72 for BRCA1 and BRCA2, respectively).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In a previous study, using a small dataset of BRCA2 variants, Karchin, Agarwal, Sali, Couch, and Beattie () find that general tools display good sensitivities but low specificities. A similar trend has been recently reported by Ernst et al (), after testing PolyPhen‐2, SIFT, Align‐GVGD, and MutationTaster2 in a set of 236 BRCA1/2 variants. These authors express concern about the moderate performance observed, particularly about the low specificities observed relative to HBOC diagnosis requirements (e.g., PolyPhen‐2: 0.67 and 0.72 for BRCA1 and BRCA2, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…In a previous study, using a small dataset of BRCA2 variants, Karchin, Agarwal, Sali, Couch, and Beattie (2008) find that general tools display good sensitivities but low specificities. A similar trend has been recently reported by Ernst et al (2018), after testing PolyPhen-2, SIFT, Align-GVGD, and…”
Section: The Performance Of Brca1-and Brca2specific Predictors In Isupporting
confidence: 88%
See 3 more Smart Citations